2015
DOI: 10.1186/s13054-015-1086-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of recombinant human soluble thrombomodulin for obstetric disseminated intravascular coagulation: a retrospective study

Abstract: IntroductionRecombinant human soluble thrombomodulin (rhTM) is a novel anti-coagulant agent that regulates the imbalanced coagulation system by reducing the excessive activation of thrombin. rhTM potentially reduces the morbidity and mortality in patients with sepsis-induced disseminated intravascular coagulation (DIC). However, the efficacy of rhTM in obstetric DIC has not yet been established. We performed this study to examine whether the administration of rhTM was a potentially effective treatment for DIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Overall, our findings indicate the key role of TM in RA treatment of blood coagulation abnormalities in cancer patients. These results are in line with recent clinical observations regarding the therapeutic effects of recombinant human thrombomodulin, an anticoagulant drug with the same external structure of TM, in the treatment of DIC [6569].…”
Section: Discussionsupporting
confidence: 88%
“…Overall, our findings indicate the key role of TM in RA treatment of blood coagulation abnormalities in cancer patients. These results are in line with recent clinical observations regarding the therapeutic effects of recombinant human thrombomodulin, an anticoagulant drug with the same external structure of TM, in the treatment of DIC [6569].…”
Section: Discussionsupporting
confidence: 88%
“…Cohorts were adjusted for the probability of treatment by using the inverse probability of treatment weighting (IPTW) approach, where each individual was weighted by the inverse probability of receiving treatment, equal to 1/PS for treated individuals and 1/(1 − PS) for control individuals. Because there is no sample loss in the IPTW approach, this design was considered appropriate for the present observational study 14 . Standardized differences 15 in the independent variables prior to and after adjustment were calculated to evaluate the balance of variables and effectiveness of the PS‐based IPTW analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Yoshihara et al. have also reported that treatment with recombinant human thrombomodulin was associated with significant improvements in platelet counts, D‐dimer, fibrinogen, and prothrombin time …”
Section: Principles In the Management Of Dic Of Obstetricsmentioning
confidence: 96%